Single‐cell RNA‐seq reveals the invasive trajectory and molecular cascades underlying glioblastoma progression - Bo Pang; Jinyuan Xu; Jing Hu; Fenghua Guo; Linyun Wan; Mingjiang Cheng; Lin Pang (Molecular Oncology, 2019)
Glioblastoma (GBM) is the most common and aggressive primary brain tumor, in which GBM stem cells (GSCs) were identified to contribute to aggressive phenotypes and poor prognosis. Yet, how GSCs progress to invasive cells remains largely unexplored. Here, we revealed the cell subpopulations with distinct functional status and the existence of cells with high invasive potential within heterogeneous primary GBM tumors. We reconstructed a branched trajectory by pseudotemporal ordering of single tumor cells, in which the root showed GSC‐like phenotype while the end displayed high invasive activity. Thus, we further determined a path along which GSCs gradually transformed to invasive cells, called the ‘stem‐to‐invasion path’. Along this path, cells showed incremental expression of GBM invasion‐associated signatures and diminishing expression of GBM stem cell markers. These findings were validated in an independent single‐cell data set of GBM. Through analyzing the molecular cascades underlying the path, we identify crucial factors controlling the attainment of invasive potential of tumor cells, including transcription factors and long noncoding RNAs. Our work provides novel insights into GBM progression, especially the attainment of invasive potential in primary tumor cells, and supports the cancer stem cell model, with valuable implications for GBM therapy.